Kajian Yuridis Pelaksanaan Sidang Elektronik di Masa Pandemic Covid-19 Ditinjau dari Perspektif Peraturan Mahkamah Agung - Dedi Dedi; Muhammad Al Habsy Ahmad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research aims to determine the mechanism of trials carried out using an electronic system based on what is regulated in Supreme Court Regulation Number. 4 of 2020 concerning Administration and Electronic Criminal Trials and determine the fulfillment of the defendant's rights in trials conducted electronically. This research uses normative research methods, which is research in the form of research on legal materials in the form of specific legislation or written laws. An electronic trial is a series of processes of examining, adjudicating, and deciding a defendant's case by a court which is carried out with the support of information and communication technology, audiovisual and other electronic means as stated in Article 1 point 12 of Supreme Court Regulation Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Court Electronically. In practice, electronic trials are the same as face-to-face trials which were previously often held, the difference being that the defendant did not take part in the trial in the courtroom, but rather the defendant took part in the problem via video teleconference call in the detention center where the defendant was detained. With the implementation of the electronic trial system, the defendant's rights are reduced in the electronic trial process which were previously regulated and guaranteed in the Criminal Code (KUHAP).